Some peculiarities of using strategic criminal analysis in planning and conducting covert investigative (detective) actions under martial law - Oliynychuk, Roman; Metelskyi, Ihor (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
Some features of the use of strategic criminal analysis during the planning and implementation of covert investigative (research) actions in the conditions of martial law are considered. The views of scientists on the categories related to the specifics of using strategic criminal analysis during the planning and implementation of covert investigative (search) actions in the conditions of martial law were analyzed. The importance and expediency of using the possibilities of strategic criminal analysis during the planning and conducting of covert investigative (research) actions in the conditions of martial law are substantiated. Some features of the use of strategic criminal analysis during the planning and implementation of covert investigative (research) actions under martial law conditions have been studied. The importance and expediency of using the possibilities of strategic criminal analysis during the planning and conducting of covert investigative (search) actions in the conditions of martial law are assessed. A number of relevant author’s conclusions have been drawn regarding some features of the use of strategic criminal analysis during the planning and implementation of covert investigative (search) actions in the conditions of martial law. An essential indicator of the effectiveness of the work of law enforcement agencies is the improvement of the quality level of their activities in terms of forecasting the development of events in the future. It is the ability and ability of law enforcement officers to predict the development of crime in the long term that will help them better «arm« for a more effective fight against this negative social phenomenon. In this aspect, special attention should be paid to the importance and expediency of using the capabilities of strategic criminal analysis when planning and carrying out covert investigative (research) actions under martial law, which will later play an important role in the fight against crime.